2016
DOI: 10.1177/0272431615602757
|View full text |Cite
|
Sign up to set email alerts
|

Body Structure and Physical Self-Concept in Early Adolescence

Abstract: In adolescence, the complexity of human ontogenesis embraces biological growth and maturation as well as mental, affective, and cognitive progress, and adaptation to the requirements of society. To accept our morphological constellation as part of our gender may prove a problem even to a child of average rate of maturation. The main purposes of the present study were to compare selected body shape factors of early adolescents belonging to different physical self-concept subgroups, and to identify those somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
0
10
0
3
Order By: Relevance
“…Adolescents lack a firm identity, go through frequent changes, experience confusion, and display comparative behaviors [61,62]. It is therefore crucial for them to establish a consistent and clear self-concept that is not based upon their appearance or body image.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents lack a firm identity, go through frequent changes, experience confusion, and display comparative behaviors [61,62]. It is therefore crucial for them to establish a consistent and clear self-concept that is not based upon their appearance or body image.…”
Section: Discussionmentioning
confidence: 99%
“…Although gender differences may be less prevalent in younger children before adolescence, boys usually show a more positive physical self-concept and higher motivation as well as better physical performance than girls (e.g., Eccles and Harold, 1991;Jacobs et al, 2002;Morano et al, 2011). In addition, several studies have revealed that children's body mass index (BMI), calculated as weight (kg) divided by height (m) squared, was closely intertwined with differences in physical self-concept (Paeratakul et al, 2002;Marsh et al, 2007b;Morano et al, 2011), motivation, and physical achievement (Trost et al, 2001;Morano et al, 2011;Zsakai et al, 2017): overweight or obese children typically demonstrate a lower physical self-concept, lower motivation, and poorer performance in physical activities than their normal-weight peers. However, it is still unclear in the literature whether children's BMI also changes the relations between physical self-concept, motivation, and physical performance (i.e., does being obese reinforce or decrease the relations?).…”
Section: Gender and Physical Differencesmentioning
confidence: 99%
“…Finally, when the relationship between body mass index and self-concept is considered, a negative and indirect relationship is seen, with a slightly stronger relation amongst girls. The association between body mass index and self-concept can be largely explained by the strong impact of body image on the physical dimension of self-concept, which, in turn, has a strong impact on the social dimension of self-concept [59,60]. The differences presented between sexes, in which males showed a stronger relation, can be explained by the fact that boys of the age examined in the present study tend to engage in physical activity competitively against their peers.…”
Section: Discussionmentioning
confidence: 99%